Deskripsi Kesiapan Guru Geografi dalam Implementasi Kurikulum Merdeka Belajar - Akbar; Andrias; La Ode Nursalam; Sitti Kasmiati (Jurnal Penelitian Pendidikan Geografi, 2024)
Senior High School 6 Kendari has problems implementing the Kurikulum Merdeka due to low human resources. The implementation of the Kurikulum Merdeka is hampered by teachers who lack literacy about technology, making it difficult to keep up with developments in learning technology in the digital era. The objectives of this research are: 1) determine teacher readiness in implementing the Kurikulum Merdeka; and 2) know the implementation of the Kurikulum Merdeka at Senior High School 6 Kendari. This type of research is descriptive qualitative research. The results of this research are as follows: 1) teacher readiness in implementing the Kurikulum Merdeka at Senior High School 6 Kendari is the action of the school in preparing facilities and infrastructure because the role of facilities and infrastructure is very important in supporting the learning process; 2) the implementation of the Kurikulum Merdeka has been carried out in classes X, XI, and XII. Things that have been implemented are project-based learning, 6 Pancasila Profiles, and subject-based learning where science and social studies subjects are combined into IPAS.